Investigation of ionic doping in all-solid-state organic electrochemical transistors - Hou, Kunqi (Nanyang Technological University, 2024)
Organic electrochemical transistors (OECTs) represent a new generation of transistors based on the electrochemical doping of conjugated semiconductors, which possess attractive features such as high transconductance and low operation voltage compared to conventional field-effect transistors. Nevertheless, the utilization of liquid electrolytes in OECTs restricts their potential applications in wearable electronics due to stability and packaging issues. Consequently, the development of all-solid-state OECTs (SSOECTs) becomes imperative to enable stable operation and expand the application scenarios of OECTs beyond bioelectronics. In this thesis, an extensive investigation of ionic doping in all-solid-state OECTs is performed for addressing the stability and scalability challenges associated with the use of liquid electrolytes. Firstly, an electrochemical annealing effect is observed in Poly (3,4- ethylenedioxythiophene)-poly (styrene sulfonate) (PEDOT:PSS)-based SSOECTs, which induces a significant change in film microstructure and carrier transport mobility, resulting in enhancement of electrical performance and thermal stability of SSOECTs. Further, we proceed to develop a universal solid polymer electrolyte based on thermoplastic polyurethane (TPU) ionic gels and showed good OECT performance with four different ion-permeable semiconductors to prove the generality of the TPU solid electrolyte. It is found that the electrochemical doping ability of the electrolyte is influenced by the hydrophilicity/hydrophobicity of the ionic liquids used in the electrolyte for various types of conjugated polymers. These transistors are also found to be robust against a wide temperature range, retaining their functionality from -50 °C to 120 °C. To demonstrate the applications of the developed SSOECTs, ‘in-electrolyte computing’ capability of our SSOECTs are assessed through tuning the parameters of the ionic circuits, e.g., ionic resistance (Rb) and gate capacitance (Cg) It is found that the charging dynamics of SSOECTs is heavily influenced by the bulk resistance of the solid electrolyte, resulting in tunable device performance with varying gate-channel distance. A 12-channel SSOECT-based multiplexer platform is further demonstrated based on this concept. Additionally, tunable transistor performance is also realized by adjusting the gate capacitance, resulting in nonvolatile SSOECT-based synaptic devices by scaling down the gate geometry. These results demonstrate a promising candidate for the developed SSOECTs for the next generation of sensory data processing and communication systems.